Past Carpathian landscape recorded in the microtopography - Affek, Andrzej. Autor (IGiPZ PAN, 2016)
The objective of this study was to map traces of the past Carpathian landscape recorded in the microtopography in the chosen study area (25 km2) within the Wiar river basin. The area comprised two deserted villages (Borysławka and Posada Rybotycka) that were abandoned and afforested after forced displacement of Ruthenian highlanders in 1940s. Three groups of complementary research methods were used: remote sensing (airborne laser scanning – ALS as the main data source), analysis of archival sources and field survey. Sky-view factor (SVF) was applied as the main visualisation technique of the LiDAR-derived DTM for mapping purposes. The results demonstrated that there are numerous, well preserved earthworks created before World War II lying under the tree canopy, such as hollow ways, agricultural terraces, remnants of settlements, border mounds etc. They form a unique cultural heritage of former inhabitants that deserves to be protected.
24 cm
Keywords: abandoned villages; earthworks; LiDAR; Austrian cadastral maps; Carpathians